Vocabulary enrichment of modern English via word-formation (on the material of the language of COVID-19 pandemic) - Karpova, Kateryna (Current issues of Ukrainian linguistics: theory and practice, 2020)
The article addresses the issue of actual changes in modern English lexicon resulting from COVID-19 pandemic. It is a common fact, that the emergence of coronavirus disease has influenced the globe in many different ways. The novel coronavirus has infected millions of people around the world since it first emerged in the Chinese city of Wuhan in December 2019. At present new ailment turned out to be a respiratory infection with significant concern for global public health hazards predominantly due to its rapid proliferation. As a result, it has compelled governments of different countries to lock down their populations to a degree unimaginable until recently. In the wake of coronavirus pandemic, we observe drastic multi-faceted changes in various spheres, including English. In this respect, the aim of current study is to find out and explore immediate namings of COVID-19-related language corpora: the disease itself and disease-related terms, words and collocations denoting mainly negative human reaction to global threat as well as of new lifestyle and working habits caused by COVID-19 outbreak. In addition, the paper presents traditional division of word-forming patterns into productive, semi-productive and non-productive and focuses on blending and abbreviation as the most productive models in modern English. In accordance with the purpose of the study, the data of the research are newly-coined namings as well as already existed lexical units of COVID-19-related vocabulary and collocations, which have been actualized or undergone semantic transformations in response to world pandemic. Language data have been collected from English dictionaries, dictionaries of modern slang, British and American media, Internet resources, and retrieved from March to September 2020. The authors resort to the following methods of scientific investigation: analysis, synthesis, systematization, taxonomy, induction, deduction, data collection and observation, lexico-semantic and contextual analysis, interpretation of dictionary definitions.
Keywords: pandemic, coronavirus COVID-19, lockdown, vocabulary, word-formation, word-forming pattern, blending, abbreviation.